Techno-Economic Analysis of the NiFe2O4 Nanoparticles for Vehicle Battery Application Using the Hydrothermal Synthesis Method - Zen, Muhammad; Haq, Fatih; Gabriella, Rachel; Putri, Silmi; Nandiyanto, Asep; Kurniawan, Tedi (Unijourn Publisher, 2021)
The purpose of this paper is to evaluate the economic and industrial scale of the production of NiFe2O4 for vehicle batteries using the hydrothermal synthesis method. The method used is to calculate gross profit margin (GPM), payback period (PBP), cumulative net present value (CNPV), total investment cost (TIC), and profitability index (PI). NiFe2O4 nanoparticles were synthesized with the main raw materials being NiCl2·6H2O, FeCl3·6H2O, and NaOH (1:2:8). Calculation results from GPM and CNPV/TIC from the NiFe2O4 industry using the hydrothermal synthesis method show the payback period (PBP) in the third year. So that in the third year onwards it can be predicted that the industry will experience profits. It is expected that NiFe2O4 can be applied on an industrial scale for Li-ion battery anodes.